2011
DOI: 10.1123/ijsnem.21.4.280
|View full text |Cite
|
Sign up to set email alerts
|

The Association of a High Drive for Thinness With Energy Deficiency and Severe Menstrual Disturbances: Confirmation in a Large Population of Exercising Women

Abstract: A high drive-for-thinness (DT) score obtained from the Eating Disorder Inventory-2 is associated with surrogate markers of energy deficiency in exercising women. The purposes of this study were to confirm the association between DT and energy deficiency in a larger population of exercising women that was previously published and to compare the distribution of menstrual status in exercising women when categorized as high vs. normal DT. A high DT was defined as a score ≥7, corresponding to the 75th percentile fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
61
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 28 publications
3
61
0
2
Order By: Relevance
“…The present study further expands upon previous reports of low RMR in women with EAMD, in whom RMR is 14-20% lower than predicted by the Harris-Benedict equation (10,15,21). However, the Harris-Benedict equation, which predicts RMR from height, weight, and age (24), does not account for differences in body tissue composition at all.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The present study further expands upon previous reports of low RMR in women with EAMD, in whom RMR is 14-20% lower than predicted by the Harris-Benedict equation (10,15,21). However, the Harris-Benedict equation, which predicts RMR from height, weight, and age (24), does not account for differences in body tissue composition at all.…”
Section: Discussionsupporting
confidence: 55%
“…As a result of these energy-conserving adaptations, resting metabolic rate (RMR) is suppressed in chronically energy-deficient women, as observed in anorexia nervosa patients who exhibit RMRs that are 20-40% lower than expected (29,38,40). Likewise, lower than expected RMRs have also been reported in women with exercise-associated menstrual disturbances (EAMD) (10,15,21), a condition caused by insufficient dietary energy intake relative to the energy expenditure of exercise (13). Because women with EAMD frequently display disrupted profiles of leptin, triiodothyronine, insulin, and other peptides involved in energy homeostasis, their lower than expected RMRs are understood as evidence of energy conservation (10,12,42).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, due to stigma associated with eating disorders, athletes may be motivated to hide their illness. An elevated Eating Disorder Inventory—drive for thinness score168 has been reported to indicate energy deficiency in exercising women,173 and amenorrhoeic athletes seem more likely to have an elevated drive for thinness score compared with eumenorrhoeic athletes 173. In order to diagnose an eating disorder, additional in-depth personal interviews must be performed 117 121 122 166.…”
Section: Screening For Relative Energy Deficiency In Sportmentioning
confidence: 99%
“…Therefore, the prevalence of eating disorders among various groups remains unclear. However, investigators 7,10,14 have consistently shown that certain groups-college-aged people, females, and athletes-may be at higher risk for developing an eating disorder than the general population.…”
mentioning
confidence: 99%